If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -0.5 * 2 Multiply -0.5 * 2 y = -1 Solving y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = -1
| 6a=126 | | 1.25=2x | | X/2=18/x | | 3x-34=2(x-18) | | 2.42 = p2 | | 3(3x-3)=21 | | (X+3)-2X=35+X | | 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 | | 10.44x=26.3 | | 5x(5+4)= | | CosX=-.08092 | | 7x+41=2x+11 | | 2x-4+3x=9 | | 63=5x+23 | | -3(3x+3)-2(1-14x)=3(6+6x) | | CosX=-.089092 | | 2x+17=-3-(-7x) | | 3/4(x-9)=-62 | | p-24=43 | | 5(z-3)=17.5 | | 180=24x-.4x^2 | | x+0.5y=0 | | -3/4(1/4) | | -3/4(1/5 | | (x+6)+(2-x)=16 | | X+(x+1)+(x+3)=41 | | -486=9(10x-5) |